Surface Immobilization of Nano-Silver on Polymeric Medical Devices to Prevent Bacterial Biofilm Formation - Andri K. Riau; Thet T. Aung; Melina Setiawan; Liang Yang; Gary H. F. Yam; Roger W. Beuerman; Subbu S. Venkatraman; Jodhbir S. Mehta (Pathogens, 2019)
Bacterial biofilm on medical devices is difficult to eradicate. Many have capitalized the anti-infective capability of silver ions (Ag+) by incorporating nano-silver (nAg) in a biodegradable coating, which is then laid on polymeric medical devices. However, such coating can be subjected to premature dissolution, particularly in harsh diseased tissue microenvironment, leading to rapid nAg clearance. It stands to reason that impregnating nAg directly onto the device, at the surface, is a more ideal solution. We tested this concept for a corneal prosthesis by immobilizing nAg and nano-hydroxyapatite (nHAp) on poly(methyl methacrylate), and tested its biocompatibility with human stromal cells and antimicrobial performance against biofilm-forming pathogens, Pseudomonas aeruginosa and Staphylococcus aureus. Three different dual-functionalized substrates—high Ag (referred to as 75:25 HAp:Ag); intermediate Ag (95:5 HAp:Ag); and low Ag (99:1 HAp:Ag) were studied. The 75:25 HAp:Ag was effective in inhibiting biofilm formation, but was cytotoxic. The 95:5 HAp:Ag showed the best selectivity among the three substrates; it prevented biofilm formation of both pathogens and had excellent biocompatibility. The coating was also effective in eliminating non-adherent bacteria in the culture media. However, a 28-day incubation in artificial tear fluid revealed a ~40% reduction in Ag+ release, compared to freshly-coated substrates. The reduction affected the inhibition of S. aureus growth, but not the P. aeruginosa. Our findings suggest that Ag+ released from surface-immobilized nAg diminishes over time and becomes less effective in suppressing biofilm formation of Gram-positive bacteria, such as S. aureus. This advocates the coating, more as a protection against perioperative and early postoperative infections, and less as a long-term preventive solution.